The effect of emotion regulation training on the level of emotion regulation of patients with chronic diseases - Ardani, Hasib; Dwidiyanti, Meidiana; Sulisno, Madya; Hartati, Elis; Sumekar, Tanjung Ayu; Fitrikasari, Alifiati (Universitas Aisyah Pringsewu, 2024)
Introduction: Chronic diseases pose significant challenges for individuals, including reduced life expectancy, increased economic burden, and heightened risk of psychological distress such as depression and anxiety. The interplay between chronic illness and negative emotions is bidirectional, where emotional distress can exacerbate physical symptoms through inflammatory processes, while the illness itself can contribute to emotional dysregulation. Emotion dysregulation is a major factor influencing stress responses, self-management adherence, and overall well-being in individuals with chronic diseases. Given this, interventions aimed at improving emotion regulation are essential to help patients manage their condition more effectively.Aim: This study aims to examine the effect of emotion regulation training therapy on improving the emotion regulation ability of individuals with chronic diseases.Methods: This study employed a quasi-experimental design with a one-group pretest-posttest approach. A total of 50 participants were recruited using purposive sampling. The intervention consisted of four emotion regulation training sessions conducted over two weeks. Data were collected using the Emotion Regulation Questionnaire (ERQ) and analyzed using a paired t-test to determine the effect of the intervention on emotion regulation levels.Results: The findings revealed a significant improvement in emotion regulation ability after the intervention, with a mean difference of 7.980 ± 3.605 (p-value = 0.000) based on the paired t-test analysis. This indicates that the emotion regulation training had a substantial impact on enhancing participants' ability to manage their emotions.Conclusion: Emotion regulation training significantly improves emotion regulation levels in patients with chronic diseases. These findings highlight the importance of integrating psychological interventions into chronic disease management to enhance patients' emotional well-being and self-management abilities. Future studies should explore the long-term effects and sustainability of emotion regulation training in diverse patient populations.